PENGARUH STCW AMANDEMEN MANILA 2010 TERHADAP PROSES RECRUITMENT ABK DI PT. BSM CREW SERVICE CENTRE INDONESIA TAHUN 2016 - Yenita Mei Anggita; Andy Wahyu Hermanto; Purwantono (Dinamika Bahari, 2017)
STCW (Standart of Training Certification and Watch keeping for Seafarers) is a basicrequirement of training, certification and watch keeping in International level that has beenratified officially, as the Manila Amendment. Based on the results of the research, from theproblems mentioned are how the recruitment process, the obstacles faced from the influence ofSTCW Amendment Manila 2010 as well as efforts to overcome the obstacles encountered.Because it is necessary to handle so that the recruitment process in the company can runsmoothly. This research uses descriptive qualitative method that describes the existing phenomena,in detail about the recruitment process at PT. BSM Crew Service Center Indonesia andexplained the obstacles and efforts undertaken to overcome these obstacles. Data are collectedby observation, including description, and document analysis results. Recruitments process conducted by the company is in accordance with establishedprocedures. However, there are still many problems during recruitment process in PT BSMCrew Service Center Indonesia that is applicant or seafarers certificate which is not inaccordance with STCW Amendment Manila 2010, the quality of applicants who do not meet thecriteria of the company and applicants who have met and passed the selection stage when thereis a required position was already on board on vessel. From the existing problems, efforts aremade, among which the company can conduct training for seafarers who have been declared tobe accepted by the company and will on-board the vessel while also giving time to ex crewseafarers who sign off from the vessel and new applicants to update the certificate and thecompany can expand the vacancy information to be expected that comes to apply more andmore.